PENGEMBANGAN MODEL PERSAMAAN STRUKTURAL DI BIDANG SOSIAL EKONOMI PERTANIAN - Sunarru Samsi Hariadi (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2001)
Structural equation models are developing, including in the field of agricultural socioeconomics. There are interrelation between one variable socio economics and other variables, or, one variable is under the influence of other variables and vice versa. More over, it can be found dependent variables more than one. Using Amos program can be analyzed the influence of many independent variables toward many dependent variables, like analysis for result of the research about factors influenced success of IDT Program (President instruction fot poverty villages) and farmers income in Gunungkidul Regency.